MENINGKATKAN LITERASI BACA SISWA KELAS 1 MELALUI PENDEKATAN PEMBELAJARAN DIFERENSIASI BERBASIS AKTIVITAS YANG BERAGAM - Theresia Startyaningsih (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The literacy interest of first-class students is still low. This is because each student has different reading abilities, varying reading interests, and different learning needs, while learning does not accommodate student learning needs so that the enthusiasm of students during learning becomes reduced and passive. To solve the problem, the researchers applied differential learning based on student learning styles: auditorium, visual and kinesthetic. The research is aimed at improving literacy and reading skills of first-class students. The class action research carried out in this study consists of pre-cycle and cycle 1. The cycle activities consist of three stages namely planning, implementation and observation, then reflection. By applying differential learning based on learning styles students cover differentiation of content and processes can experience improved literacy of cognitive learning outcomes. Based on the results of this study, it is suggested in the learning of class conditioning more so that learning runs efficiently and achieves the expected learning goals.